Public Health - Emerging and Re-Emerging Issues 2018
DOI: 10.5772/intechopen.78582
|View full text |Cite
|
Sign up to set email alerts
|

Combating Cancer Through Public Health Practice in the United States: An In-Depth Look at the National Comprehensive Cancer Control Program

Abstract: Cancer is the second leading cause of the death in the United States (U.S.). The National Comprehensive Cancer Control Program (NCCCP) is a national, public health practice program funded by the U.S. Centers for Disease Control and Prevention. The NCCCP has been planning and implementing interventions to reduce the burden of cancer since 1998. Interventions are implemented across three areas primary prevention, early detection, and survivorship using health systems and environmental changes to promote sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Participants acknowledged the role of dentists in OC prevention, however, they agreed that the role of public health professionals in raising awareness about public health issues cannot be underestimated. 28,29 Public health professionals play a key role in health promotion and disease prevention. It is a nonclinical pillar of health care system, which focuses on social, environmental, and behavioral determinants of health problem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants acknowledged the role of dentists in OC prevention, however, they agreed that the role of public health professionals in raising awareness about public health issues cannot be underestimated. 28,29 Public health professionals play a key role in health promotion and disease prevention. It is a nonclinical pillar of health care system, which focuses on social, environmental, and behavioral determinants of health problem.…”
Section: Discussionmentioning
confidence: 99%
“…Jenkins et al suggested culturally sensitive community based programs as an appropriate strategy for early detection of cancer. 33 Stewart et al (2018) summarized the National Comprehensive Cancer Control Program (NCCCP) efforts in combating cancer and highlighted the importance of multilevel collaboration to address barriers across cancer control continuum. 29 It implies that for an effective OC awareness intervention, public health professionals led multilevel efforts are necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation